Gambaran Klinik Patologi Pasien dengan Kanker Kolorektal yang Dilakukan Operasi dan Elektif di Rumah Sakit Umum Pusat Haji Adam Malik Medan - Sampe Tua Tumanggor; Bachtiar Surya; Adi Muradi (Fakultas Kedokteran USU, 2016)
Introduction : Colorectal cancer is the third most common cancer in the world with nearly 1.4 million new cases diagnosed in 2012. The incidence rate of men in higher than women in all countries. Colorectal cancer patients undergoing elective surgery more than emergency. The aim of the study was to determine the clinical features and pathological cases of colorectalcancer that were performed emergency surgery and elective at RSUP Haji Adam Malik from January 2011 to December 2013.Method : This study is a retrospective desriptive study design with secondary data from medical record of patients with colorectal cancer who had performed emergency and elective surgery at Adam Malik Hospital from January 2011 to December 2013.Result :From 40 cases underwent emergency surgery there were 22 male and 18 female, and from 139 cases undergoing elective surgery there were 77 male, 62 female. In the case of emergency 38 cases with clinical fincing of obstruction and 2 cases with peritonitis. For elective cases, 65 cases with clinical finding of defecating blood mucus, 41 cases of constipation and 33 cases with a palpable mass in the abdomen. Histopathological features in emergency cases, 22 cases with well differentiated adeno Ca and in elective cases, 81 cases with well differentiated adeno Ca.Conclusion: The most clinical features in emergency cases with obstruction were 38 cases, while for elective cases with clinical picture defecating blood mucus were 65 cases. The most histopathologic features in emergency cases with well differetiated Ca were 22 cases and in elective cases were 81 cases.Keywords : Colorectal cancer, clinical pathology, emergency and elective surgery